Doctor Foster. Season 1 [videorecording (DVD)] - Jones, Suranne, 1978-; Carvel, Bertie, 1977-; Taylor, Tom, 2001- (Warner Home Video, 2016)
It's a chilling tale of love, trust, betrayal and revenge. Dr. Gemma Foster's charmed life explodes when she suspects her husband of an affair. As dark, deceitful secrets come to light, will she live a lie for the sake of her family and career? Or take revenge and reap the consequences? Brace yourself for the truth in this gripping psychological drama.